An Efficient Separator with Low Li‐Ion Diffusion Energy Barrier Resolving Feeble Conductivity for Practical Lithium–Sulfur Batteries. Issue 40 (5th September 2019) - Lv, Xiaoxue; Lei, Tianyu; Wang, Bojun; Chen, Wei; Jiao, Yu; Hu, Yin; Yan, Yichao; Huang, Jianwen; Chu, Junwei; Yan, Chaoyi; Wu, Chunyang; Wang, Jianwei; et al.
Abstract: Due to unprecedented features including high‐energy density, low cost, and light weight, lithium–sulfur batteries have been proposed as a promising successor of lithium‐ion batteries. However, unresolved detrimental low Li‐ion transport rates in traditional carbon materials lead to large energy barrier in high sulfur loading batteries, which prevents the lithium–sulfur batteries from commercialization. In this report, to overcome the challenge of increasing both the cycling stability and areal capacity, a metallic oxide composite (NiCo2 O4 @rGO) is designed to enable a robust separator with low energy barrier for Li‐ion diffusion and simultaneously provide abundant active sites for the catalytic conversion of the polar polysulfides. With a high sulfur‐loading of 6 mg cm −2 and low sulfur/electrolyte ratio of 10, the assembled batteries deliver an initial capacity of 5.04 mAh cm −2 as well as capacity retention of 92% after 400 cycles. The metallic oxide composite NiCo2 O4 @rGO/PP separator with low Li‐ion diffusion energy barrier opens up the opportunity for lithium–sulfur batteries to achieve long‐cycle, cost‐effective operation toward wide applications in electric vehicles and electronic devices. Abstract : Based on the challenge of increasing both cycling stability and areal capacity, a metallic oxide composite (NiCo2 O4 @rGO) is designed to enable a robust separator with low energy barrier for Li‐ion diffusion and simultaneously provide abundant active sites for the catalytic conversion of the polar polysulfides.